2020
DOI: 10.1016/j.fct.2020.111805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of the novel coronavirus SARS-CoV-2 and potential anti-COVID19 pharmacological targets since the outbreak of the pandemic

Abstract: The novel coronavirus SARS-CoV-2 has emerged as a severe threat against public health and global economies. COVID-19, the disease caused by this virus, is highly contagious and has led to an ongoing pandemic. SARS-CoV-2 affects, mainly, the respiratory system, with most severe cases primarily showcasing acute respiratory distress syndrome. Currently, no targeted therapy exists, and since the number of infections and death toll keeps rising, it has become a necessity to study possible therapeutic targets. Antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 146 publications
0
31
0
Order By: Relevance
“…The urgent need of developing potential diagnostic, therapeutic, and preventive strategies till the vaccination arrives is drug repurposing. The main viral therapeutic proteins identified are spike protein (S-protein), 3C-like protease (3CL pro ), papain like protease (PL pro ), RNA-dependent RNA polymerase (RdRp), nucleocapsid protein (N-protein), transmembrane protease serine-2, envelope protein (E-protein) and the membrane (M) protein 11 . The spike protein is responsible for the interaction of virus to host cell receptor angiotensinconverting enzyme 2 (ACE2) and after the entry of the virus into the host cell, viral polyproteins are processed by 3CL pro and PL pro resulting in the release of nonstructural proteins (NSPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urgent need of developing potential diagnostic, therapeutic, and preventive strategies till the vaccination arrives is drug repurposing. The main viral therapeutic proteins identified are spike protein (S-protein), 3C-like protease (3CL pro ), papain like protease (PL pro ), RNA-dependent RNA polymerase (RdRp), nucleocapsid protein (N-protein), transmembrane protease serine-2, envelope protein (E-protein) and the membrane (M) protein 11 . The spike protein is responsible for the interaction of virus to host cell receptor angiotensinconverting enzyme 2 (ACE2) and after the entry of the virus into the host cell, viral polyproteins are processed by 3CL pro and PL pro resulting in the release of nonstructural proteins (NSPs).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, M-protein inhibits the interaction of 3-phosphoinositide-dependant protein kinase 1 (PDK1) and protein kinase B (PKB) which resulted in release of caspases which eventually causes cell death 18 . This literature survey revealed that M-protein can be a potential target for limiting and targeting the formation of virions and preventing inflammation in host cells 11,19 . Recent studies have repurposed numerous drug-like candidates against well-known targets of SARS-CoV-2 viz.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are responsible for the maturation of both nonstructural and structural viral proteins, making them a very attractive target for novel anti-coronavirus drugs. Thus, any inhibitor against these proteases (M pro or 3CL pro ) that can block the replication of SARS-CoV-2 would be effective for the development of therapeutic agents or antiviral drugs against SARS-CoV-2 [ 2 ] .…”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for facilitating and enhancing S proteinmediated cell entry and virus spread through the host mucosal cells. • SARS-CoV-2 uses a methyl transferase to cap its messenger RNAs to prevent them from being recognized by the host immune system and ensure their translation in host cells [4]. Disrupting the formation of the active methyl transferase complex and/or block its catalytic activity appears to be a potential strategy for developing COVID-19 therapeutics.…”
Section: Sars-cov-2: Understanding the Agent Factorsmentioning
confidence: 99%